Ovlivňuje motivace k podnikání vnímání podnikatelského prostředí? Případová studie z Moravskoslezského kraje - Šebestová, Jarmila (Univerzita Pardubice, 2016)
The main goal of this paper is to compare and contrast relationship between self-motivation to start-up and evaluation of business environment in Moravian-Silesian region. There were used primary research data in comparison with socio economic indicators between districts of the region. Own analysis is divided into four steps, when causal based model is presented to describe differences between two main types of motivation – push and pull. New positive trends could be identified as a source of sustainability in the area of the connection between the motivation to start-up and business environment. Regional business environment represents the supportive infrastructure for entrepreneurship such as entrepreneurship-friendly laws and regulations in the area of establishing a business, the existence of supporting services for business founders as well as for established firms. Spatial analysis is needed to find deeper connections with the location of the company and their local business condition to evaluate regional business environment in Moravian-Silesian Region. The existence of regional entrepreneurship sub-environments is one theoretically plausible explanation for spatial variations in entrepreneurship activity within districts.
Does Self-motivation to Start-up Business Affect an Evaliuation of Business Environment? Case Study from Moravian-Silesian Region
Keywords: Motivation; Moravian-Silesian Region; Entrepreneurship environment; Small business; L26; R11; C14